Veterinarians' perspectives of neurology : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatū, New Zealand - Shea, Anita (Massey University, 2024)
Negative perspectives of neurology are commonly reported in medical education and have led to concerns regarding patient care and insufficient numbers of neurologists. Most of the proposed contributors to this “neurophobia” relate to intellectual difficulty learning and applying neurology knowledge. However, most studies to date have explored neurophobia superficially and differences between how neurophobia is defined and how it is measured challenge what the term means and our understanding of why it develops. Despite this lack of clarity, there are increasing numbers of reports that cite educational interventions to combat neurophobia. While the medical and veterinary professions share many similarities, there is very little research exploring neurophobia in veterinary medicine. It is unclear whether negative perspectives of neurology are common in veterinarians, and what contributes to the development of veterinarians’ perspectives of neurology. The overarching aims of this research were to better understand veterinarians’ perspectives of neurology, how and why they develop, and the effect they can have on further learning and clinical experiences. This research investigated veterinarians’ and veterinary students’ perspectives of neurology using a mixed method approach. Thematic analysis of semi-structured interviews explored how veterinarians’ experiences, and their reactions to those experiences, contributed to their overall attitude towards neurology. Statistical analysis of subsequent surveys of veterinarians and undergraduate veterinary students focused on those with negative or positive attitudes towards neurology to further explore these differing perspectives. The findings of all studies were integrated to obtain a holistic understanding of how similar inciting experiences can lead to different attitudes towards neurology. Intellectual difficulty learning and applying neurology was reported by most participants, regardless of their attitude towards neurology. Differences between participants with negative or positive attitudes towards neurology were often dictated by the individual’s affective responses to that difficulty, which in turn were shaped by personality traits, values, professional identity, and the ability of the individual to resolve internal conflict. Resolution of internal conflict could improve one’s attitude towards neurology. In contrast to medical literature on neurophobia, these findings suggest that an individual’s attitude towards neurology is determined by the way they react to intellectual difficulty, not the difficulty itself. This distinction has implications for educational interventions for any difficult subject, not just neurology.
Keywords: veterinary, neurology, neurophobia; Veterinary neurology; Study and teaching; Nervous system; Diseases; Veterinary students; Veterinarians; Attitudes; 300904 Veterinary diagnosis and diagnostics